Wage Gaps in the Philippines: A Decomposition Analysis - Chow, Neriza (Animo Repository, 2024)
Copyright © 2024 by De La Salle University RESEARCH ARTICLE Wage Gaps in the Philippines: A Decomposition Analysis Neriza C. Chow*, Maria Fe Carmen L. Dabbay, and Mariel Monica R. Sauler De La Salle University, Manila, Philippines neriza.casas@dlsu.edu.ph The data show that, overall, the gaps between the 90th- and 10th-percentile average real wages have changed over time. The 90thpercentile average wage steadily increased from 2007 to 2017, while the 10th-percentile average increased quite drastically after 2013. In this paper, we aim to analyze the changes in these real wage differentials further to have a better understanding of the factors that may affect the wage distribution, specifically the 90/10, 90/50, and 50/10 wage gap groupings, by employing a simple wage gap analysis and the Oaxaca–Blinder decomposition on the October rounds of the Philippine Labor Force Survey from 2007 to 2017. We find that variables included in the study, namely, age, gender, location, education, and sector, barely explain the differences in the mean wage levels of the different gap groupings. Albeit small, when we consider the size of the wage differential collectively explained by the model, education has the greatest influence, followed by location and sector. The contribution of education is greatly observed in the 90/10 wage gap as compared to the other two groupings. Meanwhile, for location, a significant contribution is observed in college and high school graduate categories.